Extensibility of the arteries in man - Fulton, J. S. (The University of Edinburgh, 1930)
The thesis consists of two volumes: - VOLUME I is composed of five sections and at the beginning of each section a brief sketch is provided, showing the manner in which the subject matter of the section is arranged. Section I is introductory and consists of a brief historical outline of the subject, with some remarks on the scope and aim of the present work. Section II deals with the method. Section III contains the experimental results with a foreword on the evolution of the technique Section IV contains the results of an investigation into the histological structure of the arteries. Section V consists of a discussion on the results obtained, together with a summary and a list of references alphabetically arranged. VOLUME II is comprised of a collection of photomicrographs of sections of human arteries which have been investigated histologically, together with notes on each slide.
The extensibility of the arteries in man